The impact of e-learning on the desire to learn through increasing motivation from the point of view of the teachers of Al-Balqa Applied University - Taha Sami Othman, Rasha Ahmad Abu Odeh, Safa'a Ibrahim Al Halalmeh (Journal of engineering sciences and information technology, 2018)
The current study aimed to determine how the use of e-learning in education leads to affect students’ motivation in the field of learning and to investigate the effect of technology on students’ motivation, identifying how motivated learners are towards electronic learning, learn about e-learning features, identifying the obstacles and disadvantages of e-learning and Identifying the impact of e-learning on students’ grades. The study uses the structural equation model to empirically test the DeLone and McLean models of the success model of the information system in the university e-learning environment. Eight study hypotheses were tested using PLS analysis in survey data. The study reaches many valuable results, the most important of them is,e-learning students to succeed, they must provide an e-learning system that provides the information they need and easy-to-use information. Although the quality of the system (easy to use systems) does not directly contribute to predict personal impact, its impact is indirect. The quality of the system and the quality of the information have a positive impact on user satisfaction. The quality of the information also has a positive impact on the use of the system, which in turn has a positive effect on user satisfaction.